The Science of Emotional Intelligence - George Taukeni, Simon (IntechOpen, 2021)
Emotional intelligence (EI) is the best instrument to build stronger relationships, communicate effectively, relieve stress, overcome challenges, and achieve career and personal goals. As such, this book covers a variety of topics related to the science of EI. Chapters address the science and philosophy behind EI, using EI to cope with consequences, strategies to develop EI in early childhood education, neuromarketing, emotional responding and adversity, brain networks of emotional prosody processing, humor events and wellbeing, and much more.